(untitled) (Journal of Society of Surgeons of Nepal, 2025)
Introduction: Fistula-in-ano is a chronic distressing condition that significantly affects the quality of life. While conventional techniques(fistulectomy/fistulotomy) remain the standard treatment, sphincter-sparing procedures such as the ligation of Intersphincteric fistula tract (LIFT) and others have shown promising outcomes. This study compares the outcomes of LIFT (and its modification) with conventional techniques in the management of fistula-in-ano. Methods: A prospective observational study was conducted on 25 patients with low intersphincteric/transsphincteric fistula-in-ano at Kathmandu medical college. Data collection was done between April 1 and June 30, 2025. Twelve patients underwent modified LIFT and thirteen underwent traditional procedures. Postoperative pain, healing time, continence, and recurrence were evaluated up to 12 weeks. Statistical analysis was done using SPSS v 26.0. Results: The mean age of patients was 40.3 ± 10.7 years in the modified LIFT group and 41.7 ± 10.2 years in the other group. The modified LIFT group reported significantly lower postoperative pain (VAS: POD1 = 3.7 ± 0.5 vs 6.0 ± 0.8; POD7 = 1.3 ± 0.4 vs 2.8 ± 0.6) and faster healing. No incontinence was reported in either group. Recurrence occurred in 2 (16.7%) patients in the Modified LIFT group and 3(23.1%) in the traditional group Conclusion: Modified LIFT offers comparable healing rates with significantly less pain and faster recovery than conventional techniques, while preserving sphincter function. It appears to be an effective sphincter-sparing alternative for low anal fistulas with similar recurrence rates.